Search for new physics in aμX data at DØ using SLEUTH: A quasi-model-independent search strategy for new physics - Abbott, B; Abolins, M; Abramov, V; Acharya, B; Adams, D; Adams, M; Alves, G; Amos, N; Anderson, E; Baarmand, M; Babintsev, V; Babukhadia, L; et al. (2000)
We present a quasi-model-independent search for the physics responsible for electroweak symmetry breaking. We define final states to be studied, and construct a rule that identifies a set of relevant variables for any particular final state. A new algorithm ("SLEUTH") searches for regions of excess in those variables and quantifies the significance of any detected excess. After demonstrating the sensitivity of the method, we apply it to the semi-inclusive channel eμX collected in 108 pb-1 of pp̄ collisions at √s=1.8 TeV at the DØ experiment during 1992-1996 at the Fermilab Tevatron. We find no evidence of new high pT physics in this sample. ©2000 The American Physical Society.